Structural and functional insights into the interaction and targeting hub TMD0 of the polypeptide transporter TAPL. Issue 1 (December 2018) - Bock, Christoph; Löhr, Frank; Tumulka, Franz; Reichel, Katrin; Würz, Julia; Hummer, Gerhard; Schäfer, Lars; Tampé, Robert; Joseph, Benesh; Bernhard, Frank; Dötsch, Volker; Abele, Rupert
Abstract The ATP-binding cassette transporter TAPL translocates polypeptides from the cytosol into the lysosomal lumen. TAPL can be divided into two functional units: coreTAPL, active in ATP-dependent peptide translocation, and the N-terminal membrane spanning domain, TMD0, responsible for cellular localization and interaction with the lysosomal associated membrane proteins LAMP-1 and LAMP-2. Although the structure and function of ABC transporters were intensively analyzed in the past, the knowledge about accessory membrane embedded domains is limited. Therefore, we expressed the TMD0 of TAPL via a cell-free expression system and confirmed its correct folding by NMR and interaction studies. In cell as well as cell-free expressed TMD0 forms oligomers, which were assigned as dimers by PELDOR spectroscopy and static light scattering. By NMR spectroscopy of uniformly and selectively isotope labeled TMD0 we performed a complete backbone and partial side chain assignment. Accordingly, TMD0 has a four transmembrane helix topology with a short helical segment in a lysosomal loop. The topology of TMD0 was confirmed by paramagnetic relaxation enhancement with paramagnetic stearic acid as well as by nuclear Overhauser effects with c6-DHPC and cross-peaks with water.